PONDOK MODERN UNTUK MENINGKATKAN MINAT ORANG TUA DALAM STUDI ANAK SEPUTAR JAWA TENGAH - Muhammad, Hasan Muadz (STAI Darul Qalam Tangerang, 2024)
Pondok modern, as an evolutionary change from the time of Walisongo to the present, has emerged as a pivotal educational center transforming the educational landscape in Indonesia. Throughout history, pesantren hasn't only served as an Islamic development hub but also as a societal institution aiding communities in navigating changing times. Its extensive history signifies its enduring existence, where kyai, ustadz, and santri dedicate themselves not solely for financial motives. Nevertheless, pesantren must adapt to modern educational principles to stay pertinent. The emphasis of modern Islamic boarding schools lies in religious and cognitive education. Students undergo a significant journey influenced by various aspects, ranging from the role of teachers as exemplars in education to integrated curricula that amalgamate several distinguished programs. Time management also becomes crucial in organizing the curriculum, dividing religious and cognitive education programs into morning and evening sessions. Parents' perceptions of modern Islamic boarding schools vary, considering their children's characteristics, family background, and educational choices. Nevertheless, positive impacts are evident in students' communication skills and their handling of social-religious issues, along with the success of graduates in societal environments post-graduation. While modern Islamic boarding schools open doors for educational transformation, they remain a subject of debate regarding their role. Nonetheless, these institutions continue to fortify their position as appealing educational entities for many